Cover Image, Volume 34, Issue 3. (14th March 2023) - Zou, Jiangang; Chen, Keping; Liu, Xingbin; Xu, Yuanning; Jiang, Lingyun; Dai, Yan; Lin, Jinxuan; Hou, Xiaofeng; Qiu, Yuanhao; Himes, Adam; Lucas, Ryan; Demmer, Wade; et al.
Abstract : The cover image is based on the Original Article Clinical use conditions of lead deployment and simulated lead fracture rate in left bundle branch area pacing by Jiangang Zou MD et al., https://doi.org/10.1111/jce.15843 .